Hubungan komunikasi efektif petugas pendaftaran rawat jalan dengan kepuasan pasien di rumah sakit Advent Medan - Rangkuti, Dyna Safitri Rakhelmi; Tarigan, Andini Mentari; Rachelia , Panjaitan Hanyita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Effective communication is conveying thoughts or information from one person to another so that others grasp what the information provider means. Effective communication is required while working with patients; if it is not used effectively, it will disrupt the connection, resulting in patient discontent. This study aimed to investigate the effectiveness of outpatient registration officers' communication associated with patient satisfaction at Advent Hospital Medan 2023. The research method was quantitative, using a cross-sectional approach. The population consisted of all outpatients registered at the Outpatient Patient Registration, including 28,963 respondents. Purposive sampling was utilized in this investigation, with a total sample of 100 respondents. The Chi-Square test used univariate and bivariate data analyses. The results showed that the respect variable had a p-value value of 0,000 <0.05, the empathy variable had a p-value value of 0,000 <0,05, the audible variable had a p-value value of 0.000 <0.05, the clarity variable had a p-value value 0,000 <0.05 and the Humble variable has a P-value value of 0,000 <0.05. According to the findings of this study, respect, empathy, audibility, lucidity, and humble outpatient registration officers are associated with patient happiness. The registration officer advised to develop effective contact with patients to promote patient satisfaction with health services.